An unusual presentation of gastrointestinal stromal tumour arising from the Ileum and involving the urinary bladder - Kolap, Neeraj; Thorat, Santosh; Mhase, Akshay; Rathod, Amol; Shah, Preet (International Journal of Research in Medical Sciences, 2024)
Gastrointestinal stromal tumours (GISTs) are mesenchymal tumours originating usually from stomach and small intestines, at times from unusual sites without GI (gastrointestinal) tract involvement. GISTs frequently occur among men in the age range of 60 to 65 years. These tumours are rarely symptomatic usually discovered incidentally on radiology or intraoperatively, diagnosis is confirmed on histology and IHC (immunohistochemistry). This instance represents an unusual presentation in a 65-year-old male who presented with symptoms of fatigue, per rectal bleed and dysuria due to an underlying infraumbilical tumour which was later diagnosed as a GIST arising from the ileum concurrently involving the urinary bladder, managed successfully with neoadjuvant Imatinib therapy followed by surgical resection.